Peningkatan Pengetahuan dan Perilaku Ibu Nifas Tentang Perwatan Diri Ibu dan Bayi Baru Lahir Melalui Edukasi Kesehatan di PMB Ferawati : Penelitian - Yuli Suryanti; Adhika Wijayanti; Faulia Mauluddina; Sesilia Triana Dewi; Martina Astari; Theresia Shella Beredikta (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The postpartum period is a critical phase after childbirth that carries a high risk of complications for both mother and baby, thus requiring special attention through health education. This community service activity aimed to improve postpartum mothers’ knowledge and behavior regarding self-care and newborn care at PMB Ferawati Palembang. The activity was conducted in August 2025, involving 20 postpartum mothers through interactive lectures, discussions, and demonstrations. The pre-test and post-test results showed an increase in knowledge of self-care from 65% to 90% and newborn care from 70% to 92%. In addition, mothers began to adopt healthy behaviors such as breast care, maintaining perineal hygiene, and recognizing postpartum danger signs. Structured and interactive health education proved effective in improving knowledge and shaping healthy behavior among postpartum mothers. The active role of midwives as educators and companions was a key factor in the program’s success. This activity can serve as a sustainable intervention model to improve maternal and infant health in the community.